Pellet processing using the peel of breadfruit (Artocarpus Altilis) to be used as a biofuel - Fajardo Muñoz, Sandra Elvira; Lituma Mandujano, Víctor Miguel (Ingeniería Química y Desarrollo, 2022)
For the production of pellets, the biomass of the breadfruit peel was used, which is a biomass that is generally discarded, which will be evaluated from the Pellet Quality standard according to Standard EN 14961-2 l, when characterizing The rind of the breadfruit reflects a humidity of 48.64%, 1.3 ºBrix, pH 6.2, acidity of 0.89%, density of 0.625 g / ml and an average number of seeds of 64, the which was carried out a separation from its microns in which it was filtered until a sieve of 600-400 microns was obtained which is optimal for the production of pellets in which the yield per filtration plate was determined which was of 44% for 600 microns, for the agglutination two binder media were used which were beeswax and paraffin wax at a different weight composition of (25-75) and (50-50) in which the percentage of ash was determined from of determination of ash in food and calorific value to from ASTM D5468 in which a calorific value of 30578 j/g respectively was determined. Therefore, in the present titration work in which the objective is to make pellets using the breadfruit peel (artocarpus altilis) to be used as a biofuel, evaluating its characteristics under the norm Standard EN 14961-2 l